Unveiling the shadows of meaning: Meaning-making for perpetrators of homicide. (May 2017) - Ferrito, Martha; Needs, Adrian; Adshead, Gwen
Abstract: Human beings are thought to have unique capacities to interpret and make meaning after major life events. However this process may be complicated and difficult after events that involve anger and aggression and when dangerousness and destructiveness come to the fore. Meaning making may be especially challenging when such an event is incomprehensible to the victim's family and society, due to the perpetrator's irreversible actions and the painful awareness that a human life has been lost. Meaning-making for the perpetrator, including owning of responsibility, in the aftermath of a serious and violent crime remains under-explored; perhaps this is because violent death is an extraordinary behavior with tragic consequences on the victim that invokes enormous anxiety at the thought of exploration. The aim of this paper is to draw upon criminological, forensic and psychology literature to provide a unified perspective on meaning-making processes and what meanings are made for and by the offender in the aftermath of homicide. From the perspective of the perpetrator, challenges might include how sense can be made of the tragedy, including how a redemptive story can emerge and in turn lead to pro-social identity changes. The paper concludes by highlighting consequences and lack of adjustment following incomprehensibility. Highlights: To date, there has been little formal study of meaning-making processes for those who inflict catastrophes on others. This is a group of people who are of real concern, given what they have done and what they might do in future. Their lives are irrevocably changed after an event that changes their identity for ever, an event that professionals call the 'index offence'. Homicide perpetrators may be traumatized by the homicide itself and suffer from a range of post-traumatic psychopathology. Meaning-making is both a process and an outcome that can be applied to those who perpetrate violent offences. The review suggests that constructing meaning-making following criminal offending is at the heart of risk reduction.